Salimah's Inclusive Da'wah Strategy in Strengthening the Resilience of Muslim Families in Medan City / Strategi Dakwah Inklusif Salimah dalam Penguatan Ketahanan Keluarga Muslim di Kota Medan - Intan Suryauliani Pohan; Zulkarnain Abdurrahman (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2026)
Family resilience is the main foundation in forming a strong and prosperous society. Various social pressures such as increasing divorce rates, weak parenting patterns, and digital dependence are real threats to family resilience in Indonesia, thus demanding a more contextual and solution-based approach to da'wah. This research aims to analyze the inclusive da'wah strategy of North Sumatra Regional Leader (PW) Salimah in strengthening family resilience in Medan City and identify the impacts and challenges of its implementation. The research uses a qualitative approach with a case study design; data was collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive analysis model. This research is based on Hamka's inclusive da'wah theory in Ulfa & Efrina's research, Walsh's family resilience theory in Nafila & Cholil's research, and the perspective of women's roles in education in Ratna's research. The research results show that Salimah's inclusive, moderate and applicable da'wah strategy implemented through three main programs, namely SALSA (Sekolah Lansia Salimah,Salimah Elderly School), SISTER (Sekolah Terpadu Salimah,Salimah Integrated Mother's School), and SERASI (Sekolah Pra Nikah Salimah, Salimah Pre-Marriage School) contributes significantly to strengthening family resilience in the spiritual, psychological, social and economic dimensions. This research proves that community-based women's da'wah which positions women as agents of change is effective in building family resilience, even though it still faces challenges in the form of limited human resources, fluctuations in participants, and a lack of permanent funding.